Seroprevalence of SARS-CoV-2 Assessed by Four Chemiluminescence Immunoassays and One Immunocromatography Test for SARS-Cov-2 - Cerino, Pellegrino; Gallo, Alfonso; Pierri, Biancamaria; Buonerba, Carlo; Di Concilio, Denise; Cuomo, Maria Concetta; Vassallo, Lucia; Lo Conte, Gabriella; Coppola, Annachiara; Pizzolante, Antonio; Boccia, Giovanni; Ferrucci, Veronica; et al. (Frontiers in Public Health, 2021)
The onset of the new SARS-CoV-2 coronavirus encouraged the development of new serologic tests that could be additional and complementary to Real Time RT-PCR based assays. In such a context, the study of performances of available tests is urgently needed, as their use has just been initiated for seroprevalence assessment. The aim of this study was to compare four chemiluminescence immunoassays and one immunocromatography test for SARS-Cov-2 antibodies for the evaluation of the degree of diffusion of SARS-CoV-2 infection in Salerno Province (Campania Region, Italy). 3185 specimens from citizens were tested for anti-SARS-CoV-2 antibodies as part of a screening program. Four automated immunoassays (Abbott and Liaison SARS-CoV-2 CLIA IgG and Roche and Siemens SARS-CoV-2 CLIA IgM/IgG/IgA assays) and one lateral flow immunoassay (LFIA Technogenetics IgG-IgM COVID-19) were used. Seroprevalence in the entire cohort was 2.41%, 2.10%, 1.82% and 1.85% according to the Liaison IgG, Abbott IgG, Siemens and Roche total Ig tests, respectively. When we explored the agreement among the rapid tests and the serologic assays, we reported good agreement for Abbott, Siemens, and Roche (Cohen’s Kappa coefficient 0.69, 0.67 and 0.67, respectively), whereas we found moderate agreement for Liaison (Cohen’s Kappa coefficient 0.58). Our study showed that Abbott and Liaison SARS-CoV-2 CLIA IgG, Roche and Siemens SARS-CoV-2 CLIA IgM/IgG/IgA assays and LFIA Technogenetics IgG-IgM COVID-19 have good agreement in seroprevalence assessment. In addition, our findings indicate that the prevalence of IgG and total Ig antibodies against SARS-CoV-2 at the time of the study was as low as around 3%, likely explaining the amplitude of the current second wave.